Characterization of sites for tyrosine phosphorylation in the transforming protein of Rous sarcoma virus (pp60v-src) and its normal cellular homologue (pp60c-src). - Smart, J E (1981)
The transforming protein of Rous sarcoma virus (pp60v-src) and its normal cellular homologue (pp60c-src) appear to be protein kinases that phosphorylate tyrosine in a variety of protein substrates. In addition, pp60v-src and pp60-c-src are themselves phosphorylated on serine and tyrosine. It is likely that these phosphorylations serve to regulate the function(s) of pp60v-src and pp60c-src. We have therefore characterized the sites of tyrosine phosphorylation in the two proteins. Tyrosine phosphorylation of pp60v-src in infected cells occurs mainly (if not entirely) at residue 419 in the deduced amino acid sequence of the protein. Surrounding this residue is the sequence Leu-Ile-Glu-Asp-Asn-Glu-Tyr(P)-Thr-Ala-Arg. This peptide is distinguished by the fact that three out of the four amino acids that precede the phosphorylated tyrosine are acidic in nature. These results define what may prove to be a widely used site for tyrosine phosphorylation in the regulation of cellular function. The same site was phosphorylated when partially purified pp60v-src was used in a phosphotransfer reaction in vitro. The results with pp60c-src were more complex. The site of tyrosine phosphorylation in vitro appeared to be the same as that found in pp60v-src. By contrast, phosphorylation of pp60c-src in vivo apparently occurred at a different, and currently unidentified, tyrosine residue. It is therefore possible that pp60v-src and pp60c-src respond differently to regulatory influences in the intact cell.